Effectiveness of Family Function in Quality of Life in Elderly Patients: An Evidence Based Case Report - Muhammad Sobri Maulana (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Geriatric care is an important part in healthcare and are sometimes neglected. Family caregivers figures assume a key role in postponing and potentially forestalling standardization of chronically ill elderly patients. The role of family function in depression has been demonstrated from earlier studies, however, the part of family function in quality of life the elderly has not concentrated widely. Objective: To evaluate the connection between family function and quality of life. Methods: Literature searching was conducted through PubMed, Science Direct and Embase. Critical appraisal using appraisal sheet for prognosis from Oxford Center for Evidence Based Medicine in 2011. Results: One article was found with good validity showed that direct relationship between family function and quality of life is not associated. However, if depression is present it plays as a strong mediator between family function and quality of life. Conclusion: Family function mediated with depression plays an important role in quality of life in elderly patients.